Penerapan Prinsip-Prinsip Manajemen Mutu untuk Peningkatan Kualitas Pendidikan: Analisis Sistematis Literatur 2020–2025 - Nirmala Sari; Arifatun Nurussa’adah; Ainur Robithoh Trisnawati; Mu’allimin, Mu’allimin (Lembaga Pengembangan Kinerja Dosen, 2025)
Educational quality management has become a strategic topic in the era of globalization because it plays a crucial role in improving institutional effectiveness and learning quality. The application of quality management principles, such as Total Quality Management (TQM) and the process approach, has been implemented in various educational institutions, although the results and approaches are still varied. This study aims to systematically examine the principles and benefits of quality management in education and to answer two main questions: (1) what are the most dominant quality management principles used in education, and (2) what is the impact of implementing these principles on improving educational quality. The research method used is a Literature Review with a qualitative approach. Data were collected from Google Scholar and Publish or Perish (PoP) databases using the keywords